2018
DOI: 10.1111/1744-9987.12745
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Five Different Methods of Anti‐ABO Antibody Titration: An Aid for ABO‐Incompatible Organ Transplants

Abstract: The accurate estimation of ABO antibody titers is of the utmost importance in organ transplants involving ABO incompatibility. We aim to compare five different methods of titration and analyze the data. Samples of 48 O group blood donors who donated during the month of December 2015 to January 2016 in our institution were subjected to ABO antibody titration by five different methods: immediate spin (IS) tube titer, antihuman globulin phase tube titer, Coomb's gel card titer, gel card titer after dithiotreitol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…Both parameters are left to the hospital's discretion. There can be considerable variability in anti‐A and ‐B titer measurements between centers, in particular when different testing modalities are employed . A recent survey demonstrated that there is a range of clinical practice, with the maximum number of LTOWB units ranging from two units to as many units as a hospital has in their inventory, and the maximum titer thresholds included less than 50, less than 100, less than 128, and less than 256 .…”
Section: Discussionmentioning
confidence: 99%
“…Both parameters are left to the hospital's discretion. There can be considerable variability in anti‐A and ‐B titer measurements between centers, in particular when different testing modalities are employed . A recent survey demonstrated that there is a range of clinical practice, with the maximum number of LTOWB units ranging from two units to as many units as a hospital has in their inventory, and the maximum titer thresholds included less than 50, less than 100, less than 128, and less than 256 .…”
Section: Discussionmentioning
confidence: 99%
“…While relatively inexpensive, manual dilution is both labor intensive and subjective, conferring significant interoperator variation. For this reason, differences of less than two dilutions are generally not deemed to be significant . Unless the plasma is treated with DTT before testing, the titers assessed by gel column are generally considered to reflect a combination of IgM and IgG class antibodies .…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, differences of less than two dilutions are generally not deemed to be significant. [14][15][16][17][18][19] Unless the plasma is treated with DTT before testing, the titers assessed by gel column are generally considered to reflect a combination of IgM and IgG class antibodies. 19 This is important, given that the blood bank is generally mainly concerned about the clinical effects of incompatible IgM class isoagglutinins, while transplant physicians are generally most concerned about the clinical effects of incompatible IgG class isoagglutinins.…”
Section: Discussionmentioning
confidence: 99%
“…There are of course potential barriers to implementation of this allocation scheme. Access to reliable out of hours ABO‐antibody measurements is one concern, particularly in the light of evidence suggesting the variability in titre measurements with different techniques . Another is the perceived increased immunological risk of ABOi transplantation.…”
Section: Discussionmentioning
confidence: 99%